2000
DOI: 10.1089/15246090050020745
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Miconazole Nitrate Vaginal Ovule in the Treatment of Vulvovaginal Candidiasis: Two Single-Blind, Controlled Studies Versus Miconazole Nitrate 100 mg Cream for 7 Days

Abstract: To determine the efficacy and safety of a single-dose (1200 mg) soft gel insert (vaginal ovule) with miconazole nitrate (2%) topical cream compared with Monistat 7 (miconazole nitrate 2%) Vaginal Cream (Advanced Care Products, North Brunswick NJ) in treating vulvovaginal candidiasis (VVC), two randomized, single-blind, multicenter, controlled, comparative phase III studies were performed. Five hundred fifty-eight patients received either a single-dose miconazole nitrate (1200 mg) ovule or seven consecutive dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…The authors reported the adverse drug reaction of miconazole nitrate vaginal suppository 1,200 mg including burning, pruritus, and irritation [8,9,20]. In the present study, the adverse drug reaction rate of miconazole nitrate 1,200 mg vaginal ovule insert and oral fluconazole 150 mg was low.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…The authors reported the adverse drug reaction of miconazole nitrate vaginal suppository 1,200 mg including burning, pruritus, and irritation [8,9,20]. In the present study, the adverse drug reaction rate of miconazole nitrate 1,200 mg vaginal ovule insert and oral fluconazole 150 mg was low.…”
Section: Discussionmentioning
confidence: 41%
“…The Centers for Disease Control and Prevention recommend two doses of oral fluconazole 150 mg to treat SVVC [3]. Several studies have demonstrated that uncomplicated VVC responds well to a single dose of miconazole nitrate vaginal suppository 1,200 mg [4,5,6,7,8,9]. The effect of miconazole nitrate vaginal suppository 1,200 mg on SVVC is not known.…”
Section: Introductionmentioning
confidence: 99%
“…All were browsed according to title and abstract; however, a few randomised and prospective controlled studies were left over. 30,31,43,70,87,108,134,145 There were only three meta-analyses or Cochrane analyses 105,150,160 and two guidelines. 13,82 For this revision, another search was conducted using the same methods to identify articles from the last 5 years (as of 10.11.2013); this revealed 357 hits, with 44 review articles and 32 clinical studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A MedLine/PubMed research with the term “vulvovaginal candidosis” resulted in 2886 titles and limited to “vulvovaginal candidosis therapy studies” resulted in 237 reviews (2/2010). All were screened for title and abstract, but very few of the recent studies were randomized and/or conducted as prospective controlled trials (Fong 1992, Quereux et al 2000, Upmalis et al 2000, Lowe, Neal and Ryan‐Wenger 2004, Sobel et al 2004, Meyer, Göttlicher and Mendling 2006, Donders et al 2008). There were 3 meta‐analyses or Cochrane analyses (Pitsouni, Iavazzo and Falagas 2008, Watson et al 2002, Young and Jewell 2001) and two guidelines (Mendling and Seebacher 2008, Bond et al 2003).…”
Section: Methodsmentioning
confidence: 99%